High troponin levels and increased risk of serious cardiac complications and death in Puerto Ricans with acute myocardial infarction - Zevallos, Juan Carlos; Zevallos, Roberto; Collada, Beatriz; Marticorena, Roberto; Pandya, Reeni; Lucio Paredes, María del Mar; Lozano, Juan Manuel (Desafíos, 2015)
Objective: To examine the association of cTnI elevation and risk of serious cardiac complications and in-hospital death in Hispanics with an AMI residing in Puerto Rico. Material and methods: Patients from the Puerto Rico Heart Attack Study hospitalized during 2007, 2009, and 2011 with a validated AMI diagnosis and with cTnI obtained within the first 24-hours of admission were included for analysis. cTnI increase >10µg/L was defined as high. We utilized logistic regression modeling to examine the association of cTnI levels and serious cardiac complications (atrial/ventricular tachycardia/fibrillation, atrioventricular block, papillary muscle rupture, heart failure and cardiogenic shock) and death while controlling for potential confounders. Results: Approximately 52% (1,542) patients met the inclusion criteria. The overall mean age was 66 ± 14 years and 848 (55%) were men. After adjusting for age, gender and comorbidities, patients with high cTnI levels had almost five-times the odds of developing serious cardiac complications (OR=4.8, 95%CI=3.2-7.0; p<0.001) and twice the odds of dying (OR=2.1, 95%CI=1.3-3.3; p=0.002) than those with lower cTnI levels. Conclusion: Puerto Ricans with AMI and cTnI levels >10µg/L at admission had significantly higher odds of serious cardiac complications and death than those with lower cTnI levels.